2021
DOI: 10.1161/hypertensionaha.121.17263
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Rac1-Mineralocorticoid Receptor Pathway Contributes to Renal Injury in Salt-Loaded db/db Mice

Abstract: The progression of diabetic kidney disease (DKD), a leading cause of end-stage kidney disease, involves mineralocorticoid receptor (MR) activation. We previously identified crosstalk between the small guanosine triphosphatase (GTPase) RAS-related C3 botulinus toxin substrate 1 (Rac1) and MR, but the role of Rac1-MR pathway activation in the progression of DKD is not clear. We performed uninephrectomy on type 2 diabetic mouse models, db/db (UNx-high salt [HS] db/db … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Instead, the Rac1 inhibitor NSC23766 mimicked the antikaliuretic effects of 8-aminoguanine ( Jackson et al, 2018 ), and in vitro, we observed that both 8-aminoguanosine and 8-aminoguanine modestly reduced Rac1 activation ( Jackson et al, 2018 ). Rac1 has been shown to directly activate mineralocorticoid receptors ( Shibata et al, 2008 ; Shibata et al, 2011 ; Hirohama et al, 2021 ), a process that would increase potassium excretion. Our hypothesis is that 8-aminoguanosine and 8-aminoguanine induce antikaliuresis by a mechanism independent of PNPase inhibition and possibly in part due to inhibition of Rac1 signaling; however, because the effects of 8-aminoguanosine and 8-aminoguanine on activated Rac1 are modest, inhibition of Rac1 may not be the main mechanism by which 8-aminoguanosine and 8-aminoguanine affect potassium excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the Rac1 inhibitor NSC23766 mimicked the antikaliuretic effects of 8-aminoguanine ( Jackson et al, 2018 ), and in vitro, we observed that both 8-aminoguanosine and 8-aminoguanine modestly reduced Rac1 activation ( Jackson et al, 2018 ). Rac1 has been shown to directly activate mineralocorticoid receptors ( Shibata et al, 2008 ; Shibata et al, 2011 ; Hirohama et al, 2021 ), a process that would increase potassium excretion. Our hypothesis is that 8-aminoguanosine and 8-aminoguanine induce antikaliuresis by a mechanism independent of PNPase inhibition and possibly in part due to inhibition of Rac1 signaling; however, because the effects of 8-aminoguanosine and 8-aminoguanine on activated Rac1 are modest, inhibition of Rac1 may not be the main mechanism by which 8-aminoguanosine and 8-aminoguanine affect potassium excretion.…”
Section: Discussionmentioning
confidence: 99%
“…RAC1, also known as Rac Family Small GTPase 1, is involved in the development of hypertension, 16 including salt-sensitive 17 and obesity-related hypertension, 18 through activation of mineralocorticoid receptor (MR) signaling. 11,16 To determine whether the impaired urinary sodium excretion and hypertension in PLPS offspring were attributable to a high mineralocorticoid level, we measured plasma renin and serum aldosterone levels in 5-month-old rats.…”
Section: Rac1 Is Responsible For the Transgenerational Impaired Urina...mentioning
confidence: 99%
“…Neurohumoral stimulation by the renin–angiotensin–aldosterone system, the sympathetic nervous system, and vasopressin contribute to permanent sodium retention and an associated extracellular volume load in the development of chronic HF and kidney failure, so MR antagonism should inhibit or delay this process [ 31 , 32 , 33 ]. Indeed, finerenone has been shown to repress increased Sgk1 levels in a murine model of CKD progression in T2D [ 34 ].…”
Section: The Effects Of Finerenone’s Mechanism Of Actionmentioning
confidence: 99%
“…A previous investigation demonstrated that OPN is implicated in CKD progression, and its plasma levels are elevated from the early stages of CKD [ 60 ]. In a murine model of CKD progression in T2D (uninephrectomized mice with T2D fed a high-salt diet), finerenone offered protection from podocyte injury by reducing the expression of fibronectin, as well as inflammatory markers including MCP-1 and plasminogen activator inhibitor-1 (PAI-1), in glomeruli [ 34 ].…”
Section: The Effects Of Finerenone’s Mechanism Of Actionmentioning
confidence: 99%